A comparative study of arsenic in rice in lowland and terraced paddies in the Red River Basin, Vietnam. (7th June 2020) - Tran, Chinh T.; Le, Thoa T.; Duong, Lim T.; Dultz, Stefan; Nguyen, Minh N.
Abstract: Arsenic (As) contamination has been identified as a tangible risk related to soil and land degradation, and identifying pristine regions is, therefore, important for the long‐term safety considerations of humans. The Red River Basin is among the largest cultivation regions in Southeast Asia that provides rice for local consumers as well as for exports. While the lowland part of the Red River Delta (RRD) has been recently identified as an area suffering from As risk, little is known about the upland terrace part. In this study, terraced paddy was found to be an ecosystem with a lower accumulation of As. The median As value, x ~, in the terraced paddy soil was 2.22 mg kg −1, while almost no As was detected in the rice grain. The content of soil As of the RRD ( x ~ = 6.12 mg kg −1 ) was equal to the global average and led to a significant accumulation of As in rice grain ( x ~ = 221 μg kg −1 ). Among the soil properties, soil water‐soluble silicon (SiH2O ) appeared to be the most effective factor for reducing As translocations to rice. As the diminution of available Si can narrow the arable land that produces non or low‐As rice, this is likely an emerging factor that affects land degradation. With its low‐As rice status, the terraced paddy can be highlighted as a pristine part for rice growing. The fact that As accumulates in rice at different levels between terraced and lowland paddy regions can be considered in developing As mitigation strategies or rice repricing.